Application of α-Amino-β-fluorophosphonates in Construction of their Dipeptide Analogues - Kaźmierczak, Marcin; Dutkiewicz, Grzegorz; Cytlak, Tomasz (Synthesis, 2020)
Herein, we present application of α-amino-β-fluorophosphonates for the construction of their dipeptide analogues. α-Amino-β-fluorophosphonates were prepared in a XtalFluor-E mediated deoxyfluorination of α-hydroxy-β-aminophosphonates. The reaction proceeds through an aziridinium ion formation, which was confirmed by the formation of a hexacoordinate phosphorus compound. Moreover, the absolute configuration of the obtained compounds was determined by X-ray analysis, which proved the stereochemistry.
Keywords: fluorinated aminophosphonates; nucleophilic fluorination; fluorine; phosphorus; dipeptide analogues